Penerapan Permainan Estafet Bola Kertas Dalam Menstimulasi Perkembangan Sosial Emosional Anak di RA Nurul Almi Arrafi - Yunita Selpiyani; Nefi Darmayanti (Fakultas Tarbiyah IAI Nasional Laa Rooiba, 2023)
Learning in early childhood is never separated from games, in accordance with the tenets of early childhood education, which emphasize learning while playing or playing while learning. The purpose of play is to provide learning, but children do not experience learning as a burden as occurs through play. There are several aspects of early childhood development that are stimulated through this game. One of the games given to early childhood is the paper ball relay game. The paper ball relay game is a modified form of an interesting game and can foster the social-emotional development of children, among other aspects of child development. Classroom action research on developing social-emotional aspects of early childhood through a paper ball relay game with 10 children, was conducted at RA Nurul Ilmi Arrafi, Medan Polonia. Data obtained through observation and documentation. From several activities in this study It was discovered that children's social, emotional, and cognitive development improved where it was found that in Cycle III children were able to join groups, work together and interact with their peers. This paper ball relay game is expected to be a fun learning experience to encourage children’s social-emotional development. Keywords: Paper Ball Relay; Social Emotional Development; Early Childhood